PERBANDINGAN PENURUNAN KADAR CADMIUM (Cd) PADA KERANG DARAH (Anadara granosa) DENGAN PERENDAMAN LARUTAN JERUK NIPIS (Citrus aurantifolia) PADA BERBAGAI KONSENTRASI DAN LAMA PERENDAMAN - Delvina Sinaga; Irnawati Marsaulina; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
The Comparison of Cadmium (Cd) Content Reduction on Blood Cockle (Anadara granosa) by Soaking in Lime Acid (Citrus aurantifolia) Solution in Various Concentrate and Time Soaking. Blood cockle (Anadara granosa) can accumulate heavy metal which can endanger human organ through food chain. The most frequently heavy metal found in blood cockle is Cadmium (Cd). To reduce Cd content, it can be soaked by lime acid solution (Citrus aurantifolia).The aim of this study was to compare the reduction of Cd on blood cockle by soaking in lime acid solution in various concentration and time soaking. This research was experiment research with a Completely Randomized Design. The concentration of lime acid consisted of 3 levels (0%, 25%, and 50%) and soaking time consisted of 2 levels, namely 15 minute and 30 minute. To compare the level of Cd decreased in each treatment performed two-way anova with α =0,05. Based on research results, Cd levels before treatment was 1,20632 ppm, higher than the threshold limit value recommended by SNI No.7387: 2009 (1 ppm). There were reduction of Cd in every treatment. There are significantly difference of Cd reduction between soaking time 15 minute (0,6751±0,0894 ppm) and 30 minute (0,897±0,1745 ppm). The reduction of Cd is also significantly different (p = 0,001 ppm) between concentration 0% (0,5896 ± 0,0268 ppm) and 25% (0,8279 ± 0,157 ppm), and so is concentration 0% (0,5896 ± 0,0268 ppm) and 50% (0,8546 ± 0,097 ppm) (p = 0,001). It can be concluded that blood cockle which had been taken in Belawan river has been polluted by Cd. The most optimal concentration to reduce Cd is 25% with soaking time 30 minute (80,25%). It is suggested for other researcher to examine the nutrient value of blood cockle which has soaked by lime acid solution. Key words : blood cockle, lime solution, cadmium